Вивчення освіти: наукові візії й розрізнення - Чепак, Валентина Василівна; Чепак, Валентина Васильевна; Chepak, Valentyna V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті здійснено аналіз окремих соціогуманітарних наук щодо їх потенціалу під час вивчення освіти. Установлено спільні та відмінні риси в предметній площині, проблематиці, функціях, теоретичних засадах, тенденціях розвитку цих наук. Наголошено на необхідності подальшої інтеграції наук про освіту задля реалізації теоретичних і практичних потреб освітнього інституту. The article deals with the specific social and humanitarian sciences, whose subject matter is related to education research. This is the pedagogy, philosophy of education and sociology of education. Education from pedagogy view is a field of didactic and pedagogical ethics action. Education is considered primarily as a complex of socialization technologies, including informative and ethical components. From the philosophy of education standpoint education appears primarily as social and cultural activities at the formation of ideology and culture by the means of training and education aimed. Sociology of education is currently considering as a social institution that performs at least three basic functions: socialization, cultural, educational and developmental. In sociology education is analyzed as a sphere, which is part of the existing social relations and affects its development. The relationship of these sciences and their communication allow building a full scientific picture of the development and changes of modern education.
Study of Education: Scientific Visions and Divisions
Keywords: освіта; педагогічний підхід; філософський підхід; соціологічний підхід; освітній менеджмент; education; pedagogical approach; philosophical approach; sociological approach; educational management